Introducir reformas en el libro primero del codigo civil y en la ley de registro civil relacionadas con la identidad de los transexuales - GORDILLO CADENA, MARLENE MARISOL (2012)
Speaking of the issue of sexuality in the contemporary world, we see that there have been major and significant changes in the very conception of sexuality, because its meaning and also in the ways of living. The new lifestyle, and technology available to everyone, have acted directly to the issue of sexuality left the hiding place in which he introduced the culture and to raise the issue of sexuality in the light of day, principles and values than older ones. To save the value of sexuality has meant giving it new dimensions and in turn deal with beliefs, judgments and prejudices of various kinds. Well, sexuality does not reduce end with genitality, ie in parts of the body of the male and female for breeding. Sexuality has to do with personal, very specific social and cultural rights, among which include interpersonal communication, pleasure and enjoyment. These characteristics that make human sexuality quite different from every other living being. Whether the issue of sexuality is no less striking appearances and media sensation. But if the problem is that over emphasizes its importance from a purely sexual, without taking into account all the problems that this change will be presented from a legal perspective and legal. The very fact that several cases have been raised requesting the change of sex on birth registration book and have been aimed at the Registrar's refusal is a sign that the rule in question does not adequately meet criteria of clarity at your fingertips. It is clear that in our country there are no civilian provisions to address the issue, when in this discipline which pose the greatest legal problems. As the mention of a fact registered sex forced on birth registration in the Registry, so that disagreements will arise between sex and even admitted subjectively changed through rectification that occurs after making appropriate judicial proceedings, with which I record the time of birth registration in the books of the Civil Registry and the official documentation. In the current Constitution, already recognized many different rights in all areas, as well as recognized rights to sexual and gender difference. Since they launched the vindication of the rights of homosexuals in our country and other countries have been a number of attempts at regulation, some unsuccessful, but in our country, a breakthrough occurred with the approval and subsequent publication of the Constitution of the Republic of Ecuador in 2008 No official record by 449